Micropattern-based nerve guidance conduit with hundreds of microchannels and stem cell recruitment for nerve regeneration - Park, DoYeun; kim, dong hak; Park, Su Jeong; Choi, Jeong Ho; Seo, Yoojin; Kim, Dong-Hwee; Lee, Sang-Hoon; Hyun, Jung Keun; 류진; Jung, Youngmee; Kim, Soo Hyun (NATURE PUBLISHING GROUP, 2022)
Guiding the regrowth of thousands of nerve fibers within a regeneration-friendly environment enhances the regeneration capacity in the case of peripheral nerve injury (PNI) and spinal cord injury (SCI). Although clinical treatments are available and several studies have been conducted, the development of nerve guidance conduits (NGCs) with desirable properties, including controllable size, hundreds of nerve bundle-sized microchannels, and host stem-cell recruitment, remains challenging. In this study, the micropattern-based fabrication method was combined with stem-cell recruitment factor (substance P, SP) immobilization onto the main material to produce a size-tunable NGC with hundreds of microchannels with stem-cell recruitment capability. The SP-immobilized multiple microchannels aligned the regrowth of nerve fibers and recruited the host stem cells, which enhanced the functional regeneration capacity. This method has wide applicability in the modification and augmentation of NGCs, such as bifurcated morphology or directional topographies on microchannels. Additional improvements in fabrication will advance the regeneration technology and improve the treatment of PNI/SCI.